Identification of substandard drug products using electronic tongue: cefdinir suspension as a pilot example - Abu-Khalaf N; Zaid AN; Jaradat N; Alkilany AM; Abulateefeh SR; Al Ramahi R; Ghanem M (Dove Medical Press, 2019)
Nawaf Abu-Khalaf,1 Abdel Naser Zaid,2 Nidal Jaradat,2 Alaaldin M Alkilany,3 Samer R Abulateefeh,3 Rowa Al Ramahi,2 Mashhour Ghanem4 1Department of Agricultural Biotechnology, College of Agricultural Sciences and Technology, Palestine Technical University-Kadoorie (PTUK), Tulkarm, Palestine; 2Department of Pharmacy, Faculty of Medicine and Health Sciences, An-Najah National University, Nablus, Palestine; 3Department of Pharmaceutics and Pharmaceutical Technology, School of Pharmacy, the University of Jordan, Amman 11942, Jordan; 4Department of Regulatory, Pharmacare PLC, Ramallah, PalestineCorrespondence: Abdel Naser ZaidDepartment of Pharmacy, Faculty of Medicine and Health Sciences, An-Najah National University, B.O. Box 7, Nablus, PalestineEmail anzaid@najah.eduBackground: Electronic tongue (ET) is a well-established technology that is used to detect the taste of a food or a medicinal product and to differentiate between different products based on their tastes. In addition, it can be used to monitor environmental parameters and biochemical and biological processes.Purpose: This study aims to assess any correlation between the results of pharmacopeial quality control (ie, assay, impurities, and dissolution, etc) and ET analysis for reconstituted cefdinir (CR) suspension over 10 days (ie, shelf-life).Methods: The reconstituted CR suspension was tested for several quality attributes such as dissolution behavior, pH, assay, related substances, and microbial contamination. An HPLC analytical method was verified and then used for chemical analysis. The taste of CR reconstituted suspension was followed over 10 days and was then compared with the quality control results. Moreover, Pearson’s correlation test was used to find a correlation between chemical analysis results and ET results.Results: Pearson’s test of correlation showed a significant correlation (p-value <0.05) between the conventional chemical analysis results (% of CR, % of preservative, % of released CR, % of total impurities and % of total undefined impurities in the reconstituted suspension) with the change of their taste (ie, % pattern discrimination index). ET was able to correlate the results of stability of CR suspension with the change in the taste of the suspension during the shelf life of the reconstituted suspension.Conclusion: The obtained results may suggest the use of ET as a new tool for a rapid assessment of the general quality of a suspension. Moreover, such results would suggest the use of ET to identify fake or substandard products, especially those have been stored under inappropriate storage conditions.Keywords: electronic tongue, fake, substandard, cefdinir, taste